Efektivitas Promosi Kesehatan Menggunakan Teknologi Informasi Media Sosial - Nur Arifatus Sholihah; Nengsih Nur Olivia; Abdul Hafidzirrahman; Faridah Faridah; Wahida Sukmasari; Wahyudi Joko Suwono; Yuli Ikayanti; Yenni Anggreni (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
The rapid advancement of technology and information is significantly impacting various sectors, particularly the healthcare sector. By optimizing the use of digital media for communication, education, and the facilitation of information dissemination, this analysis aims to assess the effectiveness of health promotion through social media, driven by the high utilization of digital platforms that render them potential tools for spreading health information. The study employs a literature review methodology, utilizing articles sourced from five relevant Indonesian journals published between 2017 and 2024. The findings from these five journals indicate that the use of technology, such as social media, can yield effective outcomes in health promotion through social media interventions, emphasizing the necessity for collaboration and cooperation among all stakeholders involved. Social media can serve as an effective tool to encourage the public to achieve better health, enhance their health literacy, adhere to their care regimens, and engage in health decision-making processes.